27.2 Workbook - Operations On One Matrix - Solutions PDF
27.2 Workbook - Operations On One Matrix - Solutions PDF
27.2 Workbook - Operations On One Matrix - Solutions PDF
−x + 2y = 6
3x = y − 10
Solution:
3x = y − 10
y − 10
x=
3
Plug this value for x into the first equation, then solve for y.
−x + 2y = 6
y − 10
− + 2y = 6
3
−y + 10 + 6y = 18
5y = 8
8
y=
5
1
Plug y = 8/5 back into the equation we found for x.
y − 10
x=
3
8
5
− 10
x=
3
8 50
5
− 5
x=
3
42 1
x=− ⋅
5 3
14
x=−
5
( 5 5)
14 8
− ,
−5x + y = 8
y = 3x − 8
Solution:
2
Taking the value for y given in the second equation as y = 3x − 8, we’ll
substitute for y in the first equation.
−5x + y = 8
−5x + (3x − 8) = 8
−5x + 3x − 8 = 8
−2x = 16
x =−8
y = 3x − 8
y = 3(−8) − 8
y = − 32
(−8, − 32)
2x − y = 5
−3x + y = 7
3
Solution:
2x − y + (−3x + y) = 5 + (7)
2x − 3x = 12
−x = 12
x = − 12
−3x + y = 7
−3(−12) + y = 7
y = − 29
(−12, − 29)
x = 2y − 5
−3x + 6y = 15
Solution:
4
Multiplying the first equation by 3 gives
x = 2y − 5
3x = 6y − 15
3x − 6y − 3x + 6y = − 15 + 15
−6y + 6y = − 15 + 15
0=0
This is always true, so there are infinitely many solutions to the system of
equations.
y − 2 = − (x + 1)
y =x+1
Solution:
5
As you can see from the graphs of the two functions, the intersection
point is at (0,1), which means (0,1) is the solution to the system of
equations.
5y + x = 4
3y − 3x = 6
Solution:
6
Solve the first equation for x.
5y + x = 4
x = 4 − 5y
3y − 3x = 6
3y − 3(4 − 5y) = 6
3y − 12 + 15y = 6
18y = 18
y=1
x = 4 − 5y
x = 4 − 5(1)
x =−1
(−1,1)
7
LINEAR SYSTEMS IN THREE UNKNOWNS
2x + y − z = 3
x−y+z =0
x − 2y − 3z = 4
Solution:
[1] 2x + y − z = 3
[2] x − y + z = 0
[3] x − 2y − 3z = 4
2x + y − z + x − y + z = 3
3x + y − y + z − z = 3
3x = 3
x=1
8
Let’s plug x = 1 into equations [2] and [3] to put them in terms of y and z.
x−y+z =0
1−y+z =0
[4] −y + z = − 1
and
x − 2y − 3z = 4
1 − 2y − 3z = 4
[5] −2y − 3z = 3
3(−y + z = − 1)
−3y + 3z = − 3
−3y + 3z − 2y − 3z = 0
−3y − 2y = 0
−5y = 0
y=0
9
−2y − 3z = 3
−2(0) − 3z = 3
−3z = 3
z =−1
3x + y − z = − 2
x − 2y + 3z = 23
2x + 3y + 2z = 5
Solution:
[1] 3x + y − z = − 2
[2] x − 2y + 3z = 23
[3] 2x + 3y + 2z = 5
2(3x + y − z = − 2)
10
6x + 2y − 2z = − 4
6x + 2y − 2z + 2x + 3y + 2z = 1
6x + 2y + 2x + 3y = 1
[4] 8x + 5y = 1
3(3x + y − z = − 2)
9x + 3y − 3z = − 6
9x + 3y − 3z + x − 2y + 3z = 17
9x + 3y + x − 2y = 17
[5] 10x + y = 17
−5(10x + y = 17)
−50x − 5y = − 85
11
(8x + 5y) + (−50x − 5y) = (1) + (−85)
8x + 5y − 50x − 5y = − 84
8x − 50x = − 84
−42x = − 84
x=2
10x + y = 17
10(2) + y = 17
20 + y = 17
y =−3
Plug x = 2 and y = − 3 into any of the original equations to solve for z. We’ll
use equation [1].
3x + y − z = − 2
3(2) + (−3) − z = − 2
6−3−z =−2
3−z =−2
−z = − 5
z=5
12
Therefore, the solution to the system is (x, y, z) = (2, − 3,5).
5x − 3y + z = − 8
2x + y − 2z = − 6
−3x + 2y + 4z = 19
Solution:
[1] 5x − 3y + z = − 8
[2] 2x + y − 2z = − 6
[3] −3x + 2y + 4z = 19
2(5x − 3y + z = − 8)
10x − 6y + 2z = − 16
10x − 6y + 2z + 2x + y − 2z = − 22
13
10x − 6y + 2x + y = − 22
[4] 12x − 5y = − 22
−4(5x − 3y + z = − 8)
−20x + 12y − 4z = 32
−20x + 12y − 4z − 3x + 2y + 4z = 51
−20x + 12y − 3x + 2y = 51
12x − 5y = − 22
−5y = − 12x − 22
12 22
[6] y = x+
5 5
−23x + 14y = 51
(5 )
12 22
−23x + 14 x+ = 51
5
14
168 308
−23x + x+ = 51
5 5
53 308
x+ = 51
5 5
53x = − 53
x =−1
12 22
y= x+
5 5
12 22
y= (−1) +
5 5
12 22
y=− +
5 5
10
y=
5
y=2
Plug x = − 1 and y = 2 into any of the original equations to solve for z. We’ll
use equation [1].
5x − 3y + z = − 8
5(−1) − 3(2) + z = − 8
15
−5 − 6 + z = − 8
−11 + z = − 8
z=3
−2x + 3y − 4z = 10
4x + 3y + 2z = 4
x − 6y + 4z = − 19
Solution:
[1] −2x + 3y − 4z = 10
[2] 4x + 3y + 2z = 4
[3] x − 6y + 4z = − 19
2(4x + 3y + 2z = 4)
8x + 6y + 4z = 8
16
and then add this to equation [1] so that z will be eliminated.
8x + 6y + 4z − 2x + 3y − 4z = 18
8x + 6y − 2x + 3y = 18
6x + 9y = 18
[4] 2x + 3y = 6
−2x + 3y − 4z + x − 6y + 4z = − 9
−2x + 3y + x − 6y = − 9
[5] −x − 3y = − 9
−x − 3y = − 9
−x = − 9 + 3y
[6] x = 9 − 3y
2x + 3y = 6
2(9 − 3y) + 3y = 6
17
18 − 6y + 3y = 6
18 − 3y = 6
−3y = − 12
y=4
x = 9 − 3y
x = 9 − 3(4)
x = 9 − 12
x =−3
Plug x = − 3 and y = 4 into any of the original equations to solve for z. We’ll
use equation [2].
4x + 3y + 2z = 4
4(−3) + 3(4) + 2z = 4
−12 + 12 + 2z = 4
2z = 4
z=2
18
5. Find the unique solution to the system of equations.
2x − y + z = 9
4x − 2y + 2z = 18
−2x + y − z = − 9
Solution:
[1] 2x − y + z = 9
[2] 4x − 2y + 2z = 18
[3] −2x + y − z = − 9
2x − y + z − 2x + y − z = 0
−y + z + y − z = 0
z−z =0
0=0
When all the variables eliminate and we get a true statement, it means all
points (x, y, z) are a solution to the system. So far, this is the case with
19
equations [1] and [3]. If this also happens with equation [2], then the whole
system is an “identity” and there are infinite solutions.
Let’s check the second equation to see if this is the case. Multiply equation
[3] by 2,
2(−2x + y − z = − 9)
−4x + 2y − 2z = − 18
−4x + 2y − 2z + 4x − 2y + 2z = 0
2y − 2z − 2y + 2z = 0
−2z + 2z = 0
0=0
Since all the variables eliminate and we get a true statement, the system is
an identity and there are infinite solutions.
x + 2y − z = 9
3x + y − z = 5
−x − 4y + z = 2
20
Solution:
[1] x + 2y − z = 9
[2] 3x + y − z = 5
[3] −x − 4y + z = 2
x + 2y − z − x − 4y + z = 11
2y − 4y = 11
−2y = 11
11
[4] y = −
2
3x + y − z − x − 4y + z = 7
3x + y − x − 4y = 7
[5] 2x − 3y = 7
21
Plug equation [4] into equation [5] to solve for x.
2x − 3y = 7
( 2 )
11
2x − 3 − =7
33
2x + =7
2
4x + 33 = 14
4x = − 19
19
x=−
4
Plug in x = − 19/4 and y = − 11/2 into any of the original equations to solve
for z. We’ll use equation [3].
−x − 4y + z = 2
( 4 ) ( 2 )
19 11
− − −4 − +z =2
19 44
+ +z =2
4 2
19 + 88 + 4z = 8
4z = − 99
99
z=−
4
22
Therefore, the solution to the system is (x, y, z) = (−19/4, − 11/2, − 99/4).
23
MATRIX DIMENSIONS AND ENTRIES
[−4 8]
11 9
D=
Solution:
A = [3 5 −2 1 8]
Solution:
24
6
J= 2
7
1
Solution:
The value of J4,1 is the entry in the fourth row, first column of matrix J,
which is 1, so J4,1 = 1.
3 12
1 4
C=
9 5
−3 2
Solution:
The value of C1,2 is the entry in the first row, second column of matrix C,
which is 12, so C1,2 = 12.
25
[14 −8 6]
1 5 9
N=
Solution:
The value of N1,3 is the entry in the first row, third column of matrix N, which
is 9, so N1,3 = 9.
3 6 −7 1 0
0 9 15 3 4
S=
4 0 2 11 8
−5 8 7 9 2
Solution:
The value of S3,4 is the entry in the third row, fourth column of matrix S,
which is 11, so S3,4 = 11.
26
REPRESENTING SYSTEMS WITH MATRICES
−2x + 5y = 12
6x − 2y = 4
Solution:
The system contains the variables x and y along with a constant. Which
means the matrix will have two columns, one for each variable, plus a
column for the constants, so three columns in total. Because there are two
equations in the system, the matrix will have two rows. Plugging the
coefficients and constants into a matrix gives
[ 6 −2 4 ]
−2 5 12
A=
[ 6 −2 | 4 ]
−2 5 | 12
A=
9y − 3x + 12 = 0
27
8 − 4x = 11y
Solution:
−3x + 9y = − 12
4x + 11y = 8
The system contains the variables x and y along with a constant. Which
means the matrix will have two columns, one for each variable, plus a
column for the constants, so three columns in total. Because there are two
equations in the system, the matrix will have two rows. Plugging the
coefficients and constants into a matrix gives
[ 4 11 8 ]
−3 9 −12
D=
[ 4 11 | 8 ]
−3 9 | −12
D=
4a + 7b − 5c + 13d = 6
28
3a − 8b = − 2c + 1
Solution:
4a + 7b − 5c + 13d = 6
3a − 8b + 2c + 0d = 1
[3 −8 2 0 1]
4 7 −5 13 6
H=
[3 −8 2 0 | 1]
4 7 −5 13 | 6
H=
−2x + 4y = 9 − 6z
29
7y + 2z − 3 = − 3t − 9x
Solution:
−2x + 4y + 6z + 0t = 9
9x + 7y + 2z + 3t = 3
[ 9 7 2 3 3]
−2 4 6 0 9
M=
[ 9 7 2 3 | 3]
−2 4 6 0 | 9
M=
3x − 8y + z = 7
30
2z = 3y − 2x + 4
5y = 12 − 9x
Solution:
3x − 8y + z = 7
2x − 3y + 2z = 4
9x + 5y + 0z = 12
The system contains the variables x, y, and z, along with a constant. Which
means the augmented matrix will have three columns, one for each
variable, plus a column for the constants, so four columns in total. Because
there are three equations in the system, the matrix will have three rows.
Plugging the coefficients and constants into a matrix gives
3 −8 1 7
A = 2 −3 2 4
9 5 0 12
3 −8 1 | 7
A = 2 −3 2 | 4
9 5 0 | 12
31
6. Represent the system with a matrix called K.
−4b + 2c = 3 − 7a
9c = 4 − 2b
8a − 2c = 5b
Solution:
7a − 4b + 2c = 3
0a + 2b + 9c = 4
8a − 5b − 2c = 0
The system contains the variables a, b, and c, along with a constant. Which
means the augmented matrix will have three columns, one for each
variable, plus a column for the constants, so four columns in total. Because
there are three equations in the system, the matrix will have three rows.
Plugging the coefficients and constants into a matrix gives
32
7 −4 2 3
K= 0 2 9 4
8 −5 −2 0
7 −4 2 | 3
K= 0 2 9 | 4
8 −5 −2 | 0
33
SIMPLE ROW OPERATIONS
[8 2 1 −5]
2 6 −4 1
Solution:
[2 6 −4 1 ]
8 2 1 −5
1 2 7 −3
6 1 5 −4
−7 7 0 3
9 2 8 3
Solution:
34
The operation described by R2 ↔ R4 is switching row 2 with row 4. Nothing
will happen to rows 1 and 3. The matrix after R2 ↔ R4 is
1 2 7 −3
9 2 8 3
−7 7 0 3
6 1 5 −4
[1 6 4 ]
9 2 −7
Solution:
[3 18 12 ]
9 2 −7
[9 2 −7]
3 18 12
35
0 11 6
7 −3 9
8 8 1
6 2 4
Solution:
0 11 6
21 −9 27
8 8 1
6 2 4
0 11 6
21 −9 27
8 8 1
18 6 12
0 11 6
18 6 12
8 8 1
21 −9 27
36
5. Write the new matrix after R1 + 2R2 → R1.
[1 −5 15]
6 2 7
Solution:
[2 −10 30]
[6 + 2 2 − 10 7 + 30]
[8 −8 37]
The matrix after R1 + 2R2 → R1, which is replacing row 1 with this row we just
found, is
[1 −5 15]
8 −8 37
37
13 5 −2 9
8 2 0 6
4 1 7 −3
Solution:
[32 8 0 24]
[32 + 4 8 + 1 0 + 7 24 − 3]
[36 9 7 21]
The matrix after 4R2 + R3 → R3, which is replacing row 3 with this row we just
found, is
13 5 −2 9
8 2 0 6
36 9 7 21
38
PIVOT ENTRIES AND ROW-ECHELON FORMS
3 6 −7
[1 2 1 ]
1 2 −1
Solution:
1 2 −1
[1 2 1 ]
3 6 −7
1 2 −1
[1 2 1 ]
0 0 −4
1 2 −1
[0 0 2 ]
0 0 −4
We’ll use −(1/4)R2 → R2 to get the pivot entry in the second row.
39
1 2 −1
[0 0 2 ]
0 0 1
1 2 −1
[0 0 0 ]
0 0 1
Now all the pivot entries are 1, the zeroed-out row is at the bottom, and
the pivot entries follow a staircase pattern. Therefore, the matrix is in row-
echelon form.
2. Use row operations to put the matrix into reduced row-echelon form.
0 0 0 1
1 1 −2 0
0 0 0 0
3 0 −6 0
Solution:
0 0 0 1
1 1 −2 0
0 0 0 0
1 0 −2 0
40
After R1 ↔ R4, we get
1 0 −2 0
1 1 −2 0
0 0 0 0
0 0 0 1
1 0 −2 0
0 1 0 0
0 0 0 0
0 0 0 1
1 0 −2 0
0 1 0 0
0 0 0 1
0 0 0 0
Now all the pivot entries are 1, the zeroed-out row is at the bottom, and
the pivot entries follow a staircase pattern. All the pivot columns include
only the pivot entry, and otherwise all zero entries. Therefore, the matrix is
in reduced row-echelon form.
3. Use row operations to put the matrix into reduced row-echelon form.
1 5 2
0 −3 9
0 0 7
41
Solution:
1 5 2
0 1 −3
0 0 7
1 5 2
0 1 −3
0 0 1
1 5 2
0 1 0
0 0 1
1 5 0
0 1 0
0 0 1
1 0 0
[0 0 1]
0 1 0
42
Now all the pivot entries are 1, and follow a staircase pattern. All the pivot
columns include only the pivot entry, and otherwise only 0 entries.
Therefore, the matrix is in reduced row-echelon form.
3 2 0 9
[ ]
2 4 −3 −1
2 12 −12 1
Solution:
1 −2 3 10
[ ]
2 4 −3 −1
2 12 −12 1
1 −2 3 10
2 4 −3 −1
0 8 −9 2
1 −2 3 10
0 8 −9 −21
0 8 −9 2
43
After −R2 + R3 → R3, we get
1 −2 3 10
0 8 −9 −21
0 0 0 23
1 −2 3 10
9
0 1 − 8 − 21
8
0 0 0 23
1 −2 3 10
9
0 1 − 8 − 21
8
0 0 0 1
In this matrix, the first non-zero entry in each row is a 1, and the pivots
follow a staircase pattern that moves down and to the right. Therefore,
this matrix is in row-echelon form.
5. Use row operations to put the matrix into reduced row-echelon form.
1 −2
3 1
−3 0
2 −3
44
Solution:
1 −2
0 7
−3 0
2 −3
1 −2
0 7
0 −6
2 −3
1 −2
0 7
0 −6
0 1
1 −2
0 1
0 7
0 −6
45
1 −2
0 1
0 0
0 −6
1 −2
0 1
0 0
0 0
1 0
0 1
0 0
0 0
Now all the pivot entries are 1, the zeroed-out rows are at the bottom, the
pivot entries follow a staircase pattern, and all the pivot columns include
only the pivot entry, and otherwise all 0 entries. Therefore, the matrix is in
reduced row-echelon form.
1 0 −3 7
0 1 −2 3
−1 3 −6 −13
−5 −2 22 −28
46
Solution:
1 0 −3 7
0 1 −2 3
0 3 −9 −6
−5 −2 22 −28
1 0 −3 7
0 1 −2 3
0 3 −9 −6
0 −2 7 7
1 0 −3 7
0 1 −2 3
0 0 −3 −15
0 −2 7 7
1 0 −3 7
0 1 −2 3
0 0 −3 −15
0 0 3 13
47
1 0 −3 7
0 1 −2 3
0 0 1 5
0 0 3 13
1 0 −3 7
0 1 −2 3
0 0 1 5
0 0 0 −2
1 0 −3 7
0 1 −2 3
0 0 1 5
0 0 0 1
In this matrix, the first non-zero entry in each row is a 1, and the pivots
follow a staircase pattern. Therefore, the matrix is in row-echelon form.
48
GAUSS-JORDAN ELIMINATION
x + 2y = − 2
3x + 2y = 6
Solution:
[3 2 6 ]
1 2 −2
[0 4 −12]
1 2 −2
[0 1 −3]
1 2 −2
[0 1 −3]
1 0 4
49
The second column is done, and we can see that the solution to the linear
system is (x, y) = (4, − 3).
2x + 4y = 22
3x + 3y = 15
Solution:
[3 3 15]
2 4 22
[1 1 5 ]
1 2 11
[0 1 6 ]
1 2 11
50
[0 1 6 ]
1 0 −1
The second column is done, and we can see that the solution to the linear
system is (x, y) = (−1,6).
x − 3y − 6z = 4
y + 2z = − 2
Solution:
1 −3 −6 4
[ ]
0 1 2 −2
−4 12 21 −4
1 −3 −6 4
0 1 2 −2
0 0 −3 12
51
1 0 0 −2
[0 0 −3 12 ]
0 1 2 −2
1 0 0 −2
[0 0 1 −4]
0 1 2 −2
1 0 0 −2
0 1 0 6
0 0 1 −4
The third column is done, and we can see that the solution to the linear
system is (x, y, z) = (−2,6, − 4).
2y + 4z = 4
x + 3y + 3z = 5
2x + 7y + 6z = 10
Solution:
52
The matrix for the system is
0 2 4 4
1 3 3 5
2 7 6 10
0 1 2 2
1 3 3 5
2 7 6 10
Because the first entry in the first row is 0, swap it with the second row to
get
1 3 3 5
0 1 2 2
2 7 6 10
1 3 3 5
0 1 2 2
0 1 0 0
1 0 −3 −1
[0 1 0 0]
0 1 2 2
53
1 0 −3 −1
[0 0 2 2]
0 1 2 2
1 0 −3 −1
[0 0 1 1]
0 1 2 2
1 0 0 2
[0 0 1 1]
0 1 2 2
1 0 0 2
[0 0 1 1]
0 1 0 0
The third column is done, and we can see that the solution to the linear
system is (x, y, z) = (2,0,1).
3x + 12y + 42z = − 27
x + 2y + 8z = − 5
2x + 5y + 16z = − 6
54
Solution:
3 12 42 −27
1 2 8 −5
2 5 16 −6
1 4 14 −9
1 2 8 −5
2 5 16 −6
1 4 14 −9
0 2 6 −4
2 5 16 −6
1 4 14 −9
0 2 6 −4
0 3 12 −12
1 4 14 −9
0 1 3 −2
0 3 12 −12
55
After R1 − 4R2 → R1, the matrix is
1 0 2 −1
[0 3 12 −12]
0 1 3 −2
1 0 2 −1
0 1 3 −2
0 0 3 −6
1 0 2 −1
[0 0 1 −2]
0 1 3 −2
1 0 0 3
[0 0 1 −2]
0 1 3 −2
1 0 0 3
[0 0 1 −2]
0 1 0 4
The third column is done, and we can see that the solution to the linear
system is (x, y, z) = (3,4, − 2).
56
6. Use Gauss-Jordan elimination to find the solution to the linear system
from the rref matrix.
4x + 8y + 4z = 20
4x + 6y = 4
3x + 3y − z = 1
Solution:
4 8 4 20
4 6 0 4
3 3 −1 1
1 2 1 5
4 6 0 4
3 3 −1 1
1 2 1 5
0 2 4 16
3 3 −1 1
57
1 2 1 5
0 2 4 16
0 3 4 14
1 2 1 5
0 1 2 8
0 3 4 14
1 0 −3 −11
[0 3 4 14 ]
0 1 2 8
1 0 −3 −11
[0 0 2 10 ]
0 1 2 8
1 0 −3 −11
0 1 2 8
0 0 1 5
1 0 0 4
0 1 2 8
0 0 1 5
58
After R2 − 2R3 → R2, the matrix is
1 0 0 4
0 1 0 −2
0 0 1 5
The third column is done, and we can see that the solution to the linear
system is (x, y, z) = (4, − 2,5).
59
NUMBER OF SOLUTIONS TO THE LINEAR SYSTEM
2x − 8y = 18
−7x + 2y − 5z = − 6
3x + 2z = 1
Solution:
2 −8 0 | 18
−7 2 −5 | −6
3 0 2 | 1
Work toward putting the matrix into reduced row-echelon form, starting
with finding the pivot entry in the first row.
1 −4 0 | 9
−7 2 −5 | −6
3 0 2 | 1
60
1 −4 0 | 9
0 −26 −5 | 57
0 12 2 | −26
1 −4 0 | 9
5
0 1 26
| − 57
26
0 12 2 | −26
10 3
1 0 13
| 13
5
0 1 26
| − 57
26
4 4
0 0 − 13 | 13
10 3
1 0 13
| 13
5
0 1 26
| − 57
26
0 0 1 | −1
1 0 0 | 1
0 1 0 | −2
0 0 1 | −1
61
Therefore, there’s one unique solution to the system, (x, y, z) = (1, − 2, − 1).
−x + 3y − 5z − 8w = 2
4x − 8y + 4z + 4w = − 44
3x + 5y − 16z + w = 18
−x + y − 3z − w = 6
Solution:
−1 3 −5 −8 | 2
4 −8 4 4 | −44
3 5 −16 1 | 18
−1 1 −3 −1 | 6
Work toward putting the matrix into reduced row-echelon form, starting
with finding the pivot entry in the first row.
1 −3 5 8 | −2
4 −8 4 4 | −44
3 5 −16 1 | 18
−1 1 −3 −1 | 6
62
Zero out the rest of the first column.
1 −3 5 8 | −2
0 4 −16 −28 | −36
0 14 −31 −23 | 24
0 −2 2 7 | 4
1 −3 5 8 | −2
0 1 −4 −7 | −9
0 14 −31 −23 | 24
0 −2 2 7 | 4
1 0 −7 −13 | −29
0 1 −4 −7 | −9
0 0 25 75 | 150
0 0 −6 −7 | −14
1 0 −7 −13 | −29
0 1 −4 −7 | −9
0 0 1 3 | 6
0 0 −6 −7 | −14
63
1 0 0 8 | 13
0 1 0 5 | 15
0 0 1 3 | 6
0 0 0 11 | 22
1 0 0 8 | 13
0 1 0 5 | 15
0 0 1 3 | 6
0 0 0 1 | 2
1 0 0 0 | −3
0 1 0 0 | 5
0 0 1 0 | 0
0 0 0 1 | 2
3x − 3y + 5z = − 11
−2x + y − 2z = 5
x+y−z =9
64
Solution:
3 −3 5 | −11
−2 1 −2 | 5
1 1 −1 | 9
Work toward putting the matrix into reduced row-echelon form, starting
with finding the pivot entry in the first row.
5
1 −1 3
| − 11
3
−2 1 −2 | 5
1 1 −1 | 9
5
1 −1 3
| − 11
3
4
0 −1 3
| − 73
− 83 38
0 2 | 3
5
1 −1 3
| − 11
3
− 43 7
0 1 | 3
− 83 38
0 2 | 3
65
Zero out the rest of the second column.
1
1 0 3
| − 43
− 43 7
0 1 | 3
0 0 0 | 8
The third row tells us that 0 = 8, which can’t possibly be true. Therefore,
the system has no solutions.
−x + 6y + 4z = − 22
4x − 22y − 2z + 2w = 0
x − 6y − 5z + 3w = 5
−3y − 22z = 6
Solution:
−1 6 4 0 | −22
4 −22 −2 2 | 0
1 −6 −5 3 | 5
0 −3 −22 0 | 6
66
Work toward putting the matrix into reduced row-echelon form, starting
with finding the pivot entry in the first row.
1 −6 −4 0 | 22
4 −22 −2 2 | 0
1 −6 −5 3 | 5
0 −3 −22 0 | 6
1 −6 −4 0 | 22
0 2 14 2 | −88
0 0 −1 3 | −17
0 −3 −22 0 | 6
1 −6 −4 0 | 22
0 1 7 1 | −44
0 0 −1 3 | −17
0 −3 −22 0 | 6
1 0 38 6 | −242
0 1 7 1 | −44
0 0 −1 3 | −17
0 0 −1 3 | −126
67
1 0 38 6 | −242
0 1 7 1 | −44
0 0 1 −3 | 17
0 0 −1 3 | −126
1 0 0 120 | −888
0 1 0 22 | −163
0 0 1 −3 | 17
0 0 0 0 | −109
The third row tells that 0 = − 109, which can’t be true. Therefore, the
system has no solutions.
2x + 2y − 8z = 4
−3x − 5y + 6z = − 4
5x − y − 38z = 16
Solution:
68
2 2 −8 | 4
−3 −5 6 | −4
5 −1 −38 | 16
Work toward putting the matrix into reduced row-echelon form, starting
with finding the pivot entry in the first row.
1 1 −4 | 2
−3 −5 6 | −4
5 −1 −38 | 16
1 1 −4 | 2
0 −2 −6 | 2
0 −6 −18 | 6
1 1 −4 | 2
0 1 3 | −1
0 −6 −18 | 6
1 0 −7 | 3
0 1 3 | −1
0 0 0 | 0
Since the entire last row has only zeros, the linear system has infinitely
many solutions.
69
6. For the linear system below, determine whether it has one solution, no
solutions, or infinitely many solutions.
x + y − z + 2w = 7
4x + 2y − 6z + 2w = 16
−3x + y + 7z + 6w = 3
−x − y + 4z + 3w = 8
Solution:
1 1 −1 2 | 7
4 2 −6 2 | 16
−3 1 7 6 | 3
−1 −1 4 3 | 8
Work toward putting the matrix into reduced row-echelon form. First, zero
out the rest of the first column.
1 1 −1 2 | 7
0 −2 −2 −6 | −12
0 4 4 12 | 24
0 0 3 5 | 15
70
Find the pivot entry in the second row.
1 1 −1 2 | 7
0 1 1 3 | 6
0 4 4 12 | 24
0 0 3 5 | 15
1 0 −2 −1 | 1
0 1 1 3 | 6
0 0 0 0 | 0
0 0 3 5 | 15
1 0 −2 −1 | 1
0 1 1 3 | 6
0 0 3 5 | 15
0 0 0 0 | 0
1 0 −2 −1 | 1
0 1 1 3 | 6
5
0 0 1 3
| 5
0 0 0 0 | 0
71
7
1 0 0 3
| 11
4
0 1 0 3
| 1
5
0 0 1 3
| 5
0 0 0 0 | 0
Since the entire last row has only zeros, the linear system has infinitely
many solutions.
72
73